PELATIHAN PENGELOLAAN DANA DESA MENGGUNAKAN MICROSOFT EXCEL DI KAMPUNG GURINDA JAYA - T K Rahayu; suwarjono suwarjono; T Istanto (Musamus Devotion Journal, 2020)
The use of information technology in government has been widely distributed to regions. Information technology applied in financial sector can improve public financial services in a better quality. It depends on human ability that are expected to quickly adapt the changes in information technology development. This dedication program is held in Gurinda Jaya Village. This is one of the villages located in Jagebob District of Merauke Regency. This program began with survey to find out the current situation of the village. And continued with training program and for two days. Then monitoring and evaluating on the following week. The result is 50% participants were able to use Microsoft excel to do some calculation. And 50% rest participants still need more training and guidance